Menelisik Gejolak Spiritualitas Gereja di Tengah Pasang Surut Pandemi Covid-19: Evaluasi bagi Spiritualitas Pasca Pendemi - Romelus Blegur; Nico Pabayo Gading; Rajokiaman Sinaga (Makarios: Jurnal Teologi Kontekstual, 2023)
Even though Covid-19 appears to be receding and under control, its impact is not over. One of them is related to the spirituality of the church which has surfaced as an expression of Christian faith amid the threat of Covid-19. This article wants to examine the spirituality of the church with the aim of understanding its contents, whether it continues to develop or changes following the ups and downs of Covid-19. This study uses library research methods, both printed and digital libraries which are the source of reference. The results of the study show that the spirituality of the church still has its ups and downs according to the flow of challenges it faces. This condition occurs as it did in previous times. Therefore, the church needs to re-evaluate the weakness and fragility of its spiritual condition to reorient it towards its faith commitment which is based on God's faithfulness towards post-pandemic conditions.